To work or not to work? Effects of temporary public employment on future employment and benefits - Eva Mörk; Lillit Ottosson; Ulrika Vikman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
We evaluate a temporary public sector employment program targeted at individuals with weak labor market attachment in the City of Stockholm. Having access to rich high-quality individual-level administrative data, we apply dynamic inverse probability weighting, proposed by Van den Berg and Vikström (2021), to deal with dynamic selection into the program. We find that the program is successful in increasing employment and reducing social assistance. However, being at a regular workplace seems crucial: we find negative employment effects for participants engaged in outdoor cleaning at a workplace created especially for the program. In addition, we find that the decrease in social assistance recipiency to some extent is countered by an increase in the share receiving unemployment insurance benefits. This tendency is especially pronounced for the program with negative employment effects.
Keywords: H75; I38; J45; 330; Public sector employment programs; Social assistance; Cost-shifting; Dynamic inverse probability weighting